New design model for splitting in timber connections with one row of fasteners loaded in the parallel-to-grain direction. (15th November 2020) - Yurrita, Miguel; Cabrero, José Manuel
Highlights: Brittle failure modes may happen in timber connections loaded parallel-to-grain. Splitting is the main brittle failure in connections with one row of fasteners. A new and simple model dealing with splitting failure is proposed. The new approach clearly improves the accuracy of the existing proposals. Abstract: Timber connections with one row of fasteners can fail, as the rest of timber connections, in a ductile (yielding of the fastener and embedment of the timber) or in a brittle way (wood fracture). In this latter case, one of the most common brittle failure modes is splitting, which has been traditionally assumed to be avoided in design practice by respecting a minimum spacing between fasteners. This measure reduces the possibilities, but it does not guarantee to avoid splitting. A new model dealing with splitting for connections with one row of large diameter fasteners loaded parallel-to-grain is presented in this paper. An extensive database of tests is used to compare the new approach with the existing models and to demonstrate the reached accuracy improvement.